2014
DOI: 10.7202/1027149ar
|View full text |Cite
|
Sign up to set email alerts
|

Alimentation et réseau social : une étude sur « le goût par nécessité » en contexte social

Abstract: The knowledge of how our taste preferences in food are shaped by our social lives has largely developed without attention to the roles played by relationships with other people. While the well-known sociological work of Pierre Bourdieu highlights the relationship of economic, cultural, and social capital with food consumption, very little scholarship concerned with food has given explicit empirical attention to social network connectivity as a form of social capital. To bridge this gap, this investigation util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Food taste is a crucial part of one's identity and extensive sociological inquiry has been undertaken to understand how food choices based on liking for specific tastes are linked with social, cultural and economic contexts [33][34][35]. While Bourdieu's pioneer work puts forward the notion of social class-based conditioning of taste [33], other studies also show that a multitude of such factors as prior taste experience and repeated exposure [36], biological conditioning [37], influence of one's social network and social relationships [38], traditions of particular region and nation [39], and so forth. Expanding on Bourdieu's proposition of "cultural capital"-non-material elements characterized by symbols, ideas, tastes and preferences that accumulate throughout the life and can be utilized as resources in social action-Pachucki et al argues that tastes in food can be seen as a latent "cultural capital" shaped in large part by interpersonal mechanisms within the scope of our relationship with companions, parents and family members [38].…”
Section: Discussionmentioning
confidence: 99%
“…Food taste is a crucial part of one's identity and extensive sociological inquiry has been undertaken to understand how food choices based on liking for specific tastes are linked with social, cultural and economic contexts [33][34][35]. While Bourdieu's pioneer work puts forward the notion of social class-based conditioning of taste [33], other studies also show that a multitude of such factors as prior taste experience and repeated exposure [36], biological conditioning [37], influence of one's social network and social relationships [38], traditions of particular region and nation [39], and so forth. Expanding on Bourdieu's proposition of "cultural capital"-non-material elements characterized by symbols, ideas, tastes and preferences that accumulate throughout the life and can be utilized as resources in social action-Pachucki et al argues that tastes in food can be seen as a latent "cultural capital" shaped in large part by interpersonal mechanisms within the scope of our relationship with companions, parents and family members [38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Forero and Smith (2010) in England and Pachucki (2014) and Ochs, Pontecorvo, and Fasulo (1996) in United States observed taste as a cultural product. Forero and Smith (2010) suggested that although technology and the media were influential in transforming taste, the generational values and food ideologies were the main determining factor that shaped the tastes of the Ukrainian diaspora.…”
Section: Tastementioning
confidence: 99%
“…While privileged food discourses among US families were mainly of food as a reward and as nutrition, Italian families prioritized food as pleasure. Pachucki's (2014) study with an American population explored the influence of social relations and networks to understand food taste. According to his results, in spite of the undeniable importance of economic factors in food consumption, people's social interactions are important for constructing taste.…”
Section: Tastementioning
confidence: 99%
“…This research has shown that an individual’s food choices over a longer-term timescale can be shaped by specific friends and family members (Conklin, et al, 2014; de la Haye, Robins, Mohr, & Wilson, 2013; M. A. Pachucki, Jacques, & Christakis, 2011; M. C. Pachucki, 2014).…”
Section: Introductionmentioning
confidence: 99%